The wounded leader: The illness narratives of Boris Johnson and Donald Trump. (June 2021) - Jones, Rodney H.
Abstract: This paper analyses the COVID-19 narratives of US President Donald Trump and UK Prime Minister Boris Johnson, combining principles from applied linguistic approaches to illness narratives and sociolinguistic approaches to language and gender. It focuses specifically on the ways Johnson and Trump structured their stories to portray themselves as certain kinds of 'characters', the ways they discursively constructed agency in their narratives, and the ways they engaged in various practices of stance-taking. The analysis reveals that, although Johnson and Trump seemed to have taken very different lessons from their illnesses, the subtext of both their narratives promoted a masculinist discourse designed to depict them as 'strong leaders' and to detract attention from discussions of their reckless personal behaviour leading up to their infections and the failures of their governments to formulate coherent plans to control the pandemic.